The leucine-rich repeat signaling scaffolds Shoc2 and Erbin: cellular mechanism and role in disease - Jang, HyeIn (FEBS J, 2020)
Leucine-rich repeat-containing proteins (LRR proteins) are involved in supporting a large number of cellular functions. In this review, we summarize recent advancements in understanding functions of the LRR proteins as signaling scaffolds. In particular, we explore what we have learned about the mechanisms of action of the LRR scaffolds Shoc2 and Erbin and their roles in normal development and disease. We discuss Shoc2 and Erbin in the context of their multiple known interacting partners in various cellular processes and summarize often unexpected functions of these proteins through analysis of their roles in human pathologies. We also review these LRR scaffold proteins as promising therapeutic targets and biomarkers with potential application across various pathologies.